Analisis Pengaruh Pertumbuhan Ekonomi dan Pendapatan Asli Daerah Terhadap Indeks Pembangunan Manusia : Panel Data 23 Kabupaten/ Kota Provinsi Aceh - Isthafan Najmi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
This study aims to determine the effect of Economic Growth (PE), Regional Original Revenue (PAD) on the Human Development Index (HDI) in 23 districts/cities in Aceh province for 5 (five) years, namely 2013-2017. The method used is panel data regression analysis. The chow test results show that the best model for this panel data is the fixed effect model. This study concludes that independent variables are simultaneously significant towards the Human Development Index. Partially significant economic growth is positive for the human development index in districts/cities in Aceh province. And local original income is significantly positive towards the Human Development Index, meaning that economic growth and local revenue can increase the Human Development Index in districts/cities in Aceh province. From these findings, it can be interpreted that the ability of the independent variable can account for, 54.51% of the Index Human Development. And the remaining 45.49% is explained by other variables not included in this study. The district/city government is expected to increase economic growth and local revenue so that it will continue to contribute to improving the Human Development Index.